NAVIGATING THE INVESTMENT DILEMMA: BETWEEN SHARIA AND FRIENDSHIP TRENDS, CIREBON REGENCY EVIDENCE - Aslam; Cory Vidiati; Dini Selasi; Ahmad Munajim (Institut Agama Islam Negeri Metro, 2025)
Departing from the current social/friendship trend, where psychologically there is a fear of being left behind by other friends who are hype or better known as the term FOMO for long-term investment decisions. Which may not be from the desire and mature consideration of a mature person. Likewise, a person's income can be one of the interests of investing by setting aside between 5-15% in any form according to their basic income. It becomes interesting when discussed in fiqh. This paper describes the influence of income and social/friendship trends in investing in the study of fiqh muamalah. Using a mixed approach where primary data is analyzed quantitatively obtained from the population of Cirebon Regency, using a survey in the last 1 month. And secondary data was obtained from journal articles related to the material from the internet. Then the results were analyzed descriptively and concluded. It was found that income affects individual interest in investing in the capital market, in other ways the sphere of association / friendship is not very influential on the decision to invest in the capital market (H0 accepted). Whereas fiqh studies guide young investors to invest. The implication of this finding is for stakeholders to increase the contribution of the younger generation to invest through the capital market, not because of FOMO, but based on the consideration of financial data and facts.